Normal intellectual skills in patients with Rhombencephalosynapsis. (November 2020) - Bonnetain, Marie-France; Rougeot-Jung, Christelle; Sarret, Catherine; Lion-François, Laurence; Revol, Olivier; Peyric, Emeline; Velazquez-Dominguez, Juan; Miret, Anne; Rossi, Massimiliano; Massoud, Mona; Laurichesse - Delmas, Hélène; Guibaud, Laurent; et al.
Abstract: Objectives: Rhombencephalosynapsis (RES) is a very rare cerebellar malformation. Neurodevelopmental outcome of apparently isolated RES remains poorly documented and standardized cognitive assessment, reported in only nine published cases so far, is lacking. Prenatal counselling is challenging considering the uncertain prognosis of isolated RES. The aim of this study was to focus on cognitive and motor outcome of isolated RES with a clinical description of six new cases and a detailed review of the literature. Methods: A single-centre retrospective study of all RES patients over a 15-year period. Ataxia and fine motor skills were scored using a five-grade scale, according to the degree of disturbance of daily living. Intelligence Quotient (IQ) was established according to age-related Weschler Intelligence Scales. A systematic literature review included published cases with relevant outcome data. Results: Six new cases of apparently isolated RES were reported, including three diagnosed in prenatal settings. The onset age for walking was delayed in four patients. Three patients had head shaking and three had a strabismus. One patient had a mild motor disability, one had subtle ataxia that did not impair daily life and four patients had a normal neurological examination at the last visit. Intellectual abilities were normal in all patients (full IQ score from 90 to 142), although three had ADHD. All received standard schooling. Based on these six new cases, as well as cases from 12 publications in the literature, a total of 28 patients with non-syndromic RES were analysed. Concerning motor outcome, 72% had no complaint or minimal impairment, 16% moderate and 12% severe impairment. Concerning cognitive outcome, 68% had normal cognitive skills, 18% borderline intellectual functioning and 14% moderate to severe disability. Highlights: Rhombencephalosynapsis (RES) is a rare cerebellar malformation. Syndromic RES with obstructive hydrocephalus is associated with severe cognitive outcome. Neurodevelopmental outcome of apparently isolated RES remains poorly documented. Intellectual skills are normal in all six patients of this series of isolated RES. In the literature, two third of non-syndromic RES patients have normal cognitive skills.